Pengaruh Model Pembelajaran Kooperatif Kancing Gemerincing terhadap Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SD N 03 Pakan Labuah - Alma Fira; Desti Sartini (ARZUSIN, 2026)
Student learning motivation has been a concern in various previous studies; however, studies that specifically examine the effect of the talking chips cooperative learning model on students’ learning motivation in Islamic Religious Education subjects at the elementary school level remain limited. This study aimed to analyze the effect of the talking chips cooperative learning model on the learning motivation of fifth-grade students at SD N 03 Pakan Labuah. This study used a quantitative approach with a quasi-experimental design through a nonequivalent pretest-posttest control group design, involving 45 students selected using total sampling. Data were collected through a learning motivation questionnaire that had been tested for validity and reliability, and were then analyzed using the N-Gain test and hypothesis testing with the assistance of SPSS 27. The results showed that the implementation of the talking chips cooperative learning model had a significant effect on students’ learning motivation, with a significance value (Sig. 2-tailed) of 0.001 < 0.05 and an N-Gain score of 0.95 in the high category. These findings contribute to the development of studies on cooperative learning and learning motivation, while also expanding understanding of the importance of active participation-based learning in increasing students’ motivation. The conclusion of this study confirms that the talking chips cooperative learning model can serve as an effective interactive learning strategy in the context of Islamic Religious Education, with practical implications for teachers and schools in improving the quality of the learning process and opening opportunities for further research on other variables that influence students’ learning motivation.